Emotional impact according to the way cancer patients are conducted to the surgical center: A randomized clinical trial comparing ambulation to the stretcher - Gabriela da Silva Oliveira; Paula Moreira da Silva Sabaini; Priscila Grecca Pedrão; Vinicius Bars da Silva; Marcos Alves de Lima; Thiago Emilio da Silva Mantovani; Carlos Eduardo Mattos da Cunha Andrade; Ricardo dos Reis (PLoS ONE, 2025)
This study aimed to evaluate anxiety, depression and satisfaction of cancer patients according to the type of conduction to the surgical center. A randomized clinical trial was carried out at Barretos Cancer Hospital from 2019 to 2021. One hundred seventy-six patients were enrolled: 94 in the control group (conduction to the surgical center on a stretcher and pajamas) and 82 in the experimental group (conduction to the surgical center by ambulation in one’s own clothes). The Hospital Anxiety and Depression Scale (HADS) was used to assess the levels of anxiety and depression, and the Surgery Health Care Satisfaction Assessment Questionnaire (Sati-Cir) to assess the patient’s satisfaction. There was no difference regarding anxiety and depression symptoms between groups, 15 (18.3%) and 20 (21.3%) patients had anxiety symptoms in the ambulation group and in the stretcher group, respectively (p =  0.621). Six (7.3%) patients in the ambulation group and 4 (4.3%) met the criteria for depression (p =  0.518). Compared to those who were referred to the surgical center on a stretcher, those in the ambulation group were more often satisfied or very satisfied according to the waiting time until surgery (91.5% vs 74.5%; p =  0.008) and type of clothing, own clothes compared to pajamas (100% vs 79%; p =  0.001). When all patients were asked about their preferred method of going to the surgical center, 70.5% chose to walk in their own clothes, 28.4% preferred a stretcher, and 1.1% opted for a wheelchair (p <  0.001). The transportation method to the surgical center did not affect anxiety and depression levels in cancer patients with no or low fall risk. However, patients in the ambulation group were more satisfied with the waiting time for surgery and the type of clothing. Clinical trial registration: clinicaltrials.gov, NCT03576482, https://clinicaltrials.gov/ct2/show/NCT03576482